(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2023)
Countries resort to the international judiciary to obtain a judicial ruling that holds the force of res judicata and gives everyone his right, and in the course of considering the dispute, the international court may order precautionary measures to be taken in the event that there are circumstances that require that. Conservative measures aim to protect and preserve the rights of either one or both parties on a temporary basis until the case is completed and its final judgment is issued. Therefore, the court may order temporary precautionary measures at the request of one of the parties to the dispute or on its own initiative in the event that it deems that the disputed rights are threatened with loss or damage, and in this case the court informs the parties and the Security Council as soon as it takes such a decision, while still having the right to Amendment of measures when new circumstances arise that require it.